Burnout syndrome in professors from an academic unit of a Colombian university (2011)
ABSTRACT: Objective. To determine the prevalence of burnout syndrome, and the relationship with the type of contract under which professors work for the university, in professors of an academic unit of a public university of the city of Medellin (Colombia) in 2008.Methodology. A cross sectional descriptive study was carried out in three independent, randomized, representative samples according to the type of contract (31 full timers, 21 part timers and 43 per hours). A total of 89 professors were interviewed. To measure burnout prevalence the Maslach Burnout Inventory was used. Results. The prevalence of burnout probable cases was 19.1%, an additional 49.4% was at risk of having suffered it. According to the type of contract, full time professors had the highest prevalence (25.0%). In general, professors reported high levels of emotional tiredness and depersonalization (32.6% and 30.6% respectively), and a low level of personal accomplishment (38.2%). Conclusion. Burnout syndrome presented different type of behaviors according to the type of contract, being full time professors the ones who had the highest prevalence of the syndrome; it was expressed with higher degrees of emotional tiredness and a lower personal accomplishment.